Perfusion/ventilation mismatch during exercise in chronic heart failure: an investigation of circulatory determinants. Issue 1 (July 1995) - Banning, A. P.; Lewis, N. P.; Northridge, D. B.; Elborn, J. S.; Hendersen, A. H.
Abstract : BACKGROUND–The ventilatory cost of carbon dioxide (CO2) elimination on exercise (VE/VCO2) is increased in chronic heart failure (CHF). This reflects increased physiological dead space ventilation secondary to mismatching between perfusion and ventilation during exercise. The objectives of this study were to investigate the relation of this increased VE/VCO2 slope to the syndrome of CHF or to limitation of the exercise related increase of pulmonary blood flow, or both. PATIENTS AND METHODS–Maximal treadmill exercise tests with respiratory gas analysis were performed in 45 patients with CHF (defined as resting left ventricular ejection fraction < 40% on radionuclide scan); 15 normal controls; 23 patients with coronary artery disease and normal resting left ventricular function; and 13 pacemaker dependent patients (six with and seven without CHF) directly comparing exercise responses in rate responsive and fixed rate mode. RESULTS–Patients with CHF had a steeper VE/VCO2 slope than normal controls: this was related inversely to peak VO2 below 20 mol/min/kg. In patients with coronary artery disease in whom peak VO2 (at respiratory exchange ratio > 1) was as limited as in the patients with CHF but resting left ventricular function was normal, the VE/VCO2 slope was normal. In pacemaker dependent patients fixed rate pacing resulted in lower exercise capacity and peak VO2 than rate responsive pacing; the VE/VCO2 slope was normal in patients without CHF but steeper than normal in patients with CHF; the VE/VCO2 slope was steeper during fixed rate than during rate responsive pacing in these patients with CHF. CONCLUSIONS–These findings suggest that the perfusion/ventilation mismatch during exercise in CHF is related to the chronic consequences of the syndrome and not directly to limitation of exercise related pulmonary flow. Only when the syndrome of CHF is present can matching between perfusion and ventilation be acutely influenced by changes in pulmonary flow.